English Education Master Students' Perceptions on Teacher Written Corrective Feedback in Academic Writing - Wijaya, Kristian (LPPM Universitas Advent Indonesia, 2023)
Abstract In modern L2 academic writing enterprises, teacher-written corrective feedback can be either facilitating or debilitating depending on language teachers’ understanding, actual practices, and specific-classroom situations. Through this present small-scale qualitative investigation, the researcher attempted to exhaustively investigate English Education Master Students’ perceptions on teacher written corrective feedback in academic writing. Methodologically speaking, this current study was supported by the presence of 10 online Likert-scale questionnaire items and 5 open-ended written narrative inquiry questions. Thus, qualitative content analysis was integrated into this study to obtain more authentic data from the targeted research participants. 18 English Education Master Students, batch 2020, Sanata Dharma University were voluntarily invited to complete 10 online Likert-scale questionnaire items. Meanwhile, 3 randomly-selected interviewees from a similar research sampling were asked to accomplish 5 open-ended written narrative inquiry questions. Two major themes came to the fore after the full accomplishment of data analysis processes namely: (1) An accurate utilization of teacher written corrective feedback and (2) The beneficial values of constructive teacher written corrective feedback. Some specific concluding remarks and further recommendations were also portrayed in this study. Keywords: Teacher written corrective feedback, academic writing, graduate students, qualitative content analysis